Effect of pretreatments of camellia seeds on the quality, phenolic profile, and antioxidant capacity of camellia oil - Wang, Mei; Zhang, Yuancong; Wan, Yin; Zou, Qi; Shen, Lecheng; Fu, Guiming; Gong, Er Sheng (Frontiers in Nutrition, 2022)
Camellia oil is one of the four major woody oils in the world and has high nutritional value due to its richness in monounsaturated fatty acids (MUFAs) and bioactive substances. In order to compare the effects of pretreatments of camellia seeds on the quality, phenolic profile, and antioxidant capacity of camellia oil, three different pretreatment methods, i.e., hot air (HA), steam (ST) and puffing (PU), were used to treat the seed powder in the present study. All three pretreatments changed the internal structure of the camellia seeds. The oil yield was increased after all three pretreatments, with the highest oil yield increased by PU pretreatment (Based on the oil yield, we screened out the best conditions of the three pretreatments, HA pretreatment is 60°C for 40 min, ST pretreatment is 100°C for 15 min, PU pretreatment is 800 rpm). The fatty acids (FAs) of the oil were relatively stable, with no significant changes after three pretreatments. However, all three pretreatments had a significant effect on the acid value (AV), peroxide value (PV), and benzo(a)pyrene (Ba P) of the camellia oil. The PU and HA pretreatments could increase the tocopherol content and the total sterols content in the camellia oil. The ST and PU pretreatments significantly increased the free phenolics (FP) content, all three pretreatments reduced the contents of conjugated phenolics (CP) and insoluble-bound phenolics (IBP) in the camellia oil. The IBP made the most significant contribution to the antioxidant capacities of camellia oil. ST and PU prtreatments increased the antioxidant capacities of the total phenolics in the camellia oil. Eight phenolics in FP, CP, and IBP were significantly correlated with the antioxidant capacities of camellia oil. The results of the present study could provide some theoretical guidance for the pretreatment of camellia seeds for higher oil yield, phenolic content and enhanced antioxidant capacities of camellia oil.